2017
DOI: 10.1093/dote/dow010
|View full text |Cite
|
Sign up to set email alerts
|

Radioactive self-expanding stents for palliative management of unresectable esophageal cancer: a systematic review and meta-analysis

Abstract: Stent insertion is a feasible and safe palliative management for advanced unresectable esophageal cancer. The aim of this study is to assess the efficacy of radioactive stent for unresectable esophageal cancer compared with conventional stent. Systematic searches of the PubMed and Web of science are dated from their beginning to January 25, 2016. Studies that compared radioactive stent with conventional stent for unresectable esophageal cancer were included. The outcomes were postimplantation survival, relief … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
10
0
3

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(13 citation statements)
references
References 18 publications
0
10
0
3
Order By: Relevance
“…Compared with external beam radiotherapy (EBRT) using single/fractionated high-dose-rate irradiation, 125 I seed brachytherapy has the advantages of easy preparation, direct contact with tumor tissue, less radiation to adjacent normal tissues and a higher relative biological effect (RBE) on tumor cells (8,9). A series of studies have reported that combination therapy of 125 I seed brachytherapy and stent placement shows good tumor control and survival benefits in patients with advanced esophageal cancer (10)(11)(12). However, to the best of our knowledge, there are no studies examining the mechanisms underlying the anti-cancer effects of 125 I seed radiation in ESCC.…”
Section: Introductionmentioning
confidence: 99%
“…Compared with external beam radiotherapy (EBRT) using single/fractionated high-dose-rate irradiation, 125 I seed brachytherapy has the advantages of easy preparation, direct contact with tumor tissue, less radiation to adjacent normal tissues and a higher relative biological effect (RBE) on tumor cells (8,9). A series of studies have reported that combination therapy of 125 I seed brachytherapy and stent placement shows good tumor control and survival benefits in patients with advanced esophageal cancer (10)(11)(12). However, to the best of our knowledge, there are no studies examining the mechanisms underlying the anti-cancer effects of 125 I seed radiation in ESCC.…”
Section: Introductionmentioning
confidence: 99%
“…Although the stent implantation may treat the stenosis and maintain the patency of the esophagus within a short time, the cancer microenvironment still exists and will induce esophageal lumen restenosis [32,33]. Thus, loading anti-cancer drug on the stents and endowing the stents strong anti-cancer properties via drug release after implantation became a preferable strategy for esophageal carcinoma treatment.…”
Section: Effects Of Released 5-fu On Restenosis Related Cells' Apoptomentioning
confidence: 99%
“…For example, within the UK's National Health Service (NHS) SEMS are estimated to cost from £600-£800 ($820-$1090 USD) [26]. Whereas within China, the conventional self-expanding stents used are reported to cost just ¥2000 ($310 USD), with newer irradiated devices costing ¥4000 ($620 USD) [27]. Stenting therapy remains more affordable than alternative palliative therapies for dysphasia caused by oesophageal cancer, including LASER ablation, argon beam, and photodynamic therapy [28].…”
Section: Introductionmentioning
confidence: 99%